Pelatihan Dasar-Dasar Komputer Bagi Siswa SD Di Desa Kedungotok Wilayah Kabupaten Jombang - Ino Angga Putra; Sujono Sujono; Moh Anshori Aris Widya; Khairunnusa’ Nur Muslimah; Lailatul Jannah; Mohammad Deffan Afandi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The objectives of this service activity include a) increasing students' basic komputer mastery and b) helping improve students' skills in using komputers. This service activity was carried out at SDN Kedungotok, Tembelang District from October 26 – to October 30, 2021. This activity was attended by 30 class V students. This service activity used discussion and training methods. Discussion activities are carried out by asking questions to the participants and training activities are carried out with basic komputer training for the participants. The results of community service activities showed that 67% of students in the high category in using and operating komputers and 33% of students in the moderate category in using and operating komputers. In the aspect of the ability to use Microsoft word the lowest average value with a value of 2.9 or less.